The undrained strength of some thawed permafrost soils - Nixon, John F.; Hanna, Alan J. (Canadian Geotechnical Journal, 1979)
A large number of undrained shear strengths have been measured for thawed, undrained permafrost samples obtained from the Niglintgak Peninsula area of the Mackenzie Delta, N.W.T. The samples are mostly deltaic silts, with a few clay tills, and cover a wide range of depths, water contents, and frozen density. The undrained shear strengths of the thawed samples have been correlated with water content, frozen density, and sample depth. For these soil types, the strength is shown to decrease to zero at frozen densities of less than about 1670 kg/m 3 and at water contents greater than about 35–42%. In the Niglintgak area, the undrained shear strength of the thawed samples below a depth of 10 m becomes relatively constant in the range of 23–43 kPa. This corresponds to a frozen density range of 1780–1870 kg/m 3 , and previous experience with soils of this nature indicates that the corresponding thaw settlement at these depths would be less than 10%.